2015
DOI: 10.1186/s40413-015-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

2015 update of the evidence base: World Allergy Organization anaphylaxis guidelines

Abstract: The World Allergy Organization (WAO) Guidelines for the assessment and management of anaphylaxis provide a unique global perspective on this increasingly common, potentially life-threatening disease. Recommendations made in the original WAO Anaphylaxis Guidelines remain clinically valid and relevant, and are a widely accessed and frequently cited resource. In this 2015 update of the evidence supporting recommendations in the Guidelines, new information based on anaphylaxis publications from January 2014 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
344
2
36

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(393 citation statements)
references
References 149 publications
2
344
2
36
Order By: Relevance
“…4). 1, 31, 32, 33 Early injection of adrenaline for anaphylaxis, defined as injection before ER arrival, can significantly reduce the likelihood of hospital admission, as compared with initial injection after arrival at the ER 34. Although no human studies regarding the timing of treatment for anaphylaxis could be found, analysis of 92 deaths related to anaphylaxis showed that adrenaline was given prior to cardiac arrest in only 22 of the cases (24%) 35.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…4). 1, 31, 32, 33 Early injection of adrenaline for anaphylaxis, defined as injection before ER arrival, can significantly reduce the likelihood of hospital admission, as compared with initial injection after arrival at the ER 34. Although no human studies regarding the timing of treatment for anaphylaxis could be found, analysis of 92 deaths related to anaphylaxis showed that adrenaline was given prior to cardiac arrest in only 22 of the cases (24%) 35.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
“…This evidence supports the importance of early adrenaline injection. The beneficial effect of adrenaline results from its action on systemically distributed adrenaline receptors 32. Its α1 agonist vasoconstrictor effects prevent and relieve airway edema, hypotension, and shock; its β1 agonist chronotropic and ionotropic effects increase the rate and force of cardiac contractions, and its β2 agonist effects lead to bronchodilation.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
“…29 Las causas más comunes de la anafilaxia en los niños son: a) alimentos: leche, huevos, nueces, cacahuetes, soja y pescado; b) picadura de insecto: abejas y hormigas (himenópteros); y c) fármacos: antiinflamatórios no hormonales y antibióticos (betalactámicos). 30 Los síntomas comienzan entre cinco y 30 minutos después de la exposición al agente causal pero, excepcionalmente, pueden aparecer después de unas horas. La mayoría de las veces existe participación de la piel, las mucosas o ambas (urticaria generalizada, picazón o enrojecimiento, edema de los labios, lengua y úvula) y al menos uno de los siguientes síntomas:…”
Section: Reacción Anafiláticaunclassified
“…The antihistamines could be helpful in management of children with anaphylaxis as a second or third treatment line [74]. The intramuscular administration of the first generation antihistamines (e.g.…”
Section: Anaphylaxismentioning
confidence: 99%